2015
DOI: 10.1177/0956797615569578
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence on Risk Perception During Adolescence

Abstract: Adolescence is a period of life in which peer relationships become increasingly important. Adolescents have a greater likelihood of taking risks when they are with peers rather than alone. In this study, we investigated the development of social influence on risk perception from late childhood through adulthood. Five hundred and sixty-three participants rated the riskiness of everyday situations and were then informed about the ratings of a social-influence group (teenagers or adults) before rating each situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
294
4
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 310 publications
(343 citation statements)
references
References 41 publications
20
294
4
5
Order By: Relevance
“…People’s risk perceptions seem to be affected by social influence (Knoll, Magis-Weinberg, Speekenbrink, & Blakemore, 2015). People decide on their reaction from listening and watching what others say and do.…”
Section: Disaster Risk Communication and Pre-event Strategies: Implemmentioning
confidence: 99%
See 1 more Smart Citation
“…People’s risk perceptions seem to be affected by social influence (Knoll, Magis-Weinberg, Speekenbrink, & Blakemore, 2015). People decide on their reaction from listening and watching what others say and do.…”
Section: Disaster Risk Communication and Pre-event Strategies: Implemmentioning
confidence: 99%
“…All age groups, except 12–14-year-olds, are more influenced by adults, which is consistent with other studies showing that expertise and status are strong predictors of social influence (Driskell & Mullen, 1990; Engelmann, Moore, Monica Capra, & Berns, 2012; Jetten, Hornsey, & Adarves-Yorno, 2006). When it comes to the young adolescents, on the other hand, this group values more what other teenagers say (Knoll et al, 2015). It is likely, therefore, that interventions directed towards younger age groups should emphasize social influence to a larger extent and adjust the programmes accordingly.…”
Section: Disaster Risk Communication and Pre-event Strategies: Implemmentioning
confidence: 99%
“…Previous research has shown that susceptibility to social influence is at its highest in late childhood (approximately age 8–10 years) then gradually decreases across the adolescent years (approximately 11–18 years) and into adulthood (19 years and above; Knoll, Leung, Foulkes, & Blakemore, 2017; Knoll, Magis‐Weinberg, Speekenbrink, & Blakemore, 2015; Steinberg & Monahan, 2007; Sumter, Bokhorst, Steinberg, & Westenberg, 2009). As such, relative to adults, children and adolescents are particularly susceptible to being influenced by others.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing that peers are engaging in substance use (alcohol, tobacco and illicit drugs) increases the likelihood of adolescent substance use (Lundborg, 2006). Children and adolescents, compared to adults, are also more likely to change their perception of risky behaviours based on other people's perception of those risks (Knoll et al., 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation